Final Results of Local-Regional Control and Late Toxicity of RTOG 90-03; A Randomized Trial of Altered Fractionation Radiation for Locally Advanced Head And Neck Cancer - Beitler, Jonathan J (Int J Radiat Oncol Biol Phys, 2014)
PURPOSE: To test whether altered radiation fractionation schemes improved local-regional control (LRC) rates for patients with squamous cell cancers (SCC) of the head and neck when compared to standard fractionation (SFX) of 70 Gy. PATIENTS AND METHODS: Patients with stage III or IV (or stage II base of tongue) SCC were randomized to 4 treatment arms: (1) SFX-70 Gy/35 daily fxns/7 week; (2) HFX-81.6 Gy/68 BID fxns/7 weeks; (3) AFX-S 67.2 Gy/42 fxns/6 weeks with a 2 week rest after 38.4 Gy; and (4) AFX-C 72 Gy/42 fxns/6 weeks. n=1,076. The 3 experimental arms were to be compared to SFX. RESULTS: With patients censored for LRC at 5 years, only the comparison of HFX with SFX was significantly different (HFX: Hazard Ratio-0.79(0.62–1.00), p=0.05; AFX-C 0.82 (0.65–1.05), p=0.11). Censored at 5 years, HFX improved Overall Survival (OS) (Hazard Ratio 0.81, p=0.05). Prevalence of any Grade 3, 4, or 5 toxicity at 5 years, any feeding tube use after 180 days, or feeding tube use at 1 year did not differ significantly when the experimental arms were compared to SFX. When 7 week treatments were compared to 6 week treatments, accelerated fractionation appeared to increase Grade 3, 4 or 5 toxicity at 5 years (p=0.06). Looking at the worst toxicity per patient by treatment only the AFX-C arm seemed to trend worse than the SFX arm when comparing Grade 0–2 vs. 3–5 toxicity(p=0.09). CONCLUSIONS: At 5 years, only HFX improved LRC & OS for patients with locally advanced SCC without increasing late toxicity.